Bukan sekedar warisan: Islam sebagai nafas budaya yang terus hidup - camelia, navila (Maliki Interdisciplinary Journal, 2026)
Cultural Islam in Indonesia has developed through a dialogical process between Islamic teachings and long-standing local traditions. This article examines the dynamics of the relationship between Islam and culture by analyzing historical, anthropological,and sociological aspects that shape religious practices within Indonesian society. The discussion includes the integration of Islamic values into local traditions, the role of symbols and rituals such as slametan and Bhuju’ Malem, the contribution of Islamic educational institutions in maintaining cultural continuity, and contemporary challenges arising from purification movements,globalization, and digital media. The study reveals that cultural Islam is not merely a historical legacy but an adaptive socio-religious force that continues to transform through societal creativity and digital development. These findings highlight the importance of strengthening cultural da'wah, revitalizing traditions through digital platforms, and promoting religious moderation to ensure that Islam remains relevant, inclusive, and rooted in Indonesia’s cultural identity.